2013
DOI: 10.1371/journal.pone.0067487
|View full text |Cite
|
Sign up to set email alerts
|

IgE Reactivity of Blue Swimmer Crab (Portunus pelagicus) Tropomyosin, Por p 1, and Other Allergens; Cross-Reactivity with Black Tiger Prawn and Effects of Heating

Abstract: Shellfish allergy is a major cause of food-induced anaphylaxis, but the allergens are not well characterized. This study examined the effects of heating on blue swimmer crab (Portunus pelagicus) allergens in comparison with those of black tiger prawn (Penaeus monodon) by testing reactivity with shellfish-allergic subjects' serum IgE. Cooked extracts of both species showed markedly increased IgE reactivity by ELISA and immunoblotting, and clinical relevance of IgE reactivity was confirmed by basophil activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 43 publications
9
74
0
1
Order By: Relevance
“…Since tropomyosin is heat-stable, both raw and cooked crab are possible sources for aerosolised tropomyosin (Jeebhay et al 2001;Lopata and Jeebhay 2013). Antibody reactivity of crustacean tropomyosin can also increase after heating, a possible result of protein denaturation and exposure of new epitopes, aggregation and chemical modifications Abramovitch et al 2013). A study involving snow crab processing found more aerosolised allergen when workers were handling cooked crab than raw which is in line with the results of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Since tropomyosin is heat-stable, both raw and cooked crab are possible sources for aerosolised tropomyosin (Jeebhay et al 2001;Lopata and Jeebhay 2013). Antibody reactivity of crustacean tropomyosin can also increase after heating, a possible result of protein denaturation and exposure of new epitopes, aggregation and chemical modifications Abramovitch et al 2013). A study involving snow crab processing found more aerosolised allergen when workers were handling cooked crab than raw which is in line with the results of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Since tropomyosin is heat-stable, both raw and cooked crab are sources of aerosolized tropomyosin (Jeebhay et al, 2001;Lopata and Jeebhay, 2013). Antibody reactivity of crustacean tropomyosin can also increase after heating, a possible result of protein denaturation and exposure to new epitopes, aggregation, and chemical modifications (Abramovitch et al, 2013;Kamath et al, 2013). Workers handling cooked crab may therefore have an increased risk of developing food sensitivities to crab.…”
Section: Processing and Occupational Exposurementioning
confidence: 99%
“…3-D). Of these, shrimp with IgE reactivity of 43%, is indeed the most common causative agent in seafood allergy [19]. Significant differences in the mean allergen-specific IgE levels of the allergic and control subjects were observed.…”
Section: Figmentioning
confidence: 99%